Giant paraovarian cyst in a child complicated with torsion - Kostov Miloš; Mijović Žaklina; Mihailović Dragan (Vojnosanitetski Pregled)
Background. A variety of benign cyst may occur in and around the ovary and broad ligament and may simulate serous cystadenomas. The majority of broad ligament and paraovarian epithelial tumors are serous neoplasms of low malignant potential and presented with a pelvic mass with or without ascites or pain, but without involvement of the ovary. Ovarian torsion and paraovarian serous cystadenoma are rarely reported. Case report. We presented a case of giant paraovarian cyst in an 14-year-old girl, with characteristics of serous cystadenomas grossly and microscopically, and complicated with double adnexal torsion. A computed tomography scan showed large hypodense cystic mass (measuring 30 × 26 × 12 cm), occupying the whole abdominal cavity, with no adhesion to the surrounding organs. Conclusion. Precise clinical data as well as pathological examinations based on immunohistochemical stainings were important in making the diagnosis. These rare cystic lesions of para/mesoovarian location in children and their unclear histogenesis might be a histopathological diagnostical problem.